A CASE OF ACUTE CEREBELLAR ATAXIA DUE TO EPSTEIN–BARR VIRUS AND REVIEW OF THE LITERATURE. (29th November 2012) - McColgan, P; McCarthy, C; Martin, PJ
Abstract : Background: The differential diagnosis of acute cerebellar ataxia in a young adult includes vascular, inflammatory, toxic, neoplastic, paraneoplastic, genetic and infective causes. Neurological complications of EBV are rare, but include Acute Cerebellar Ataxia, Guillain–Barré syndrome, meningitis, encephalitis, cranial nerve palsies, optic neuritis and transverse myelitis. Case Report: We present a case of a 17-year-old male who presented with acute cerebellar ataxia occurring before the onset of tonsillitis and lymphadenopathy. Serological testing confirmed acute EBV infection. Conclusion: EBV can cause cerebellitis even without its systemic manifestations. The diagnosis is based on finding EBV VCA IgM antibodies in serum rather than CSF. In most cases, the prognosis is good, with complete recovery; however, clinicians must be aware of the risk of cerebellar swelling and hydrocephalus.